Implementation of Effective Packaging Principles Using rPET Bottles in Bottled Water: A Review - Ilham Ramadon; Hariest Ayubi; Kelvin Then; Kent Pranata Tjandra; Nathania Angelica Kristiawan; Nurhayati (SEAS (Sustainable Environment Agricultural Science), 2026)
This literature review explores the use of recycled polyethylene terephthalate (rPET) bottles to implement effective packaging principles in the bottled drinking water industry. Using a narrative review of scientific literature, industry reports, and case studies, the study highlights that rPET reduces greenhouse gas emissions, energy consumption, and reliance on fossil resources while promoting circular economy practices through bottle-to-bottle recycling. Properly processed rPET retains sufficient mechanical, thermal, and barrier properties for beverage packaging and meets food safety standards. Key challenges include material degradation, quality variability, and consumer perception, which require technological innovation and efficient waste management. Industrial examples, such as PMKN in Indonesia, demonstrate successful rPET integration, label-free designs, and compliance with safety regulations. Overall, rPET adoption illustrates a balance of technical performance, environmental sustainability, and economic feasibility in effective packaging.